2019
DOI: 10.1002/jmri.26963
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of quantitative diffusion parameters in the pathological grading of hepatocellular carcinoma: A meta‐analysis

Abstract: Background: Accurate preoperative assessment of the pathological grade of hepatocellular carcinoma (HCC) could greatly benefit prognostic predictions. Purpose: To assess and compare the diagnostic accuracy of the apparent diffusion coefficient (ADC) and tissue diffusivity (D) for the noninvasive pathological grading of HCC. Study Type: Meta-analysis. Data Sources: PubMed/Medline, EMBASE, the Web of Science, and the Cochrane Library were searched to find related original articles published up to May 30, 2019. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…IVIM imaging can reflect the characteristics of lesions in terms of cell density, microcirculation perfusion, and tissue complexity (18). As reported previously, a decrease in both ADC and D values may be attributed to the increased cellular density, nuclear-tocytoplasmic ratios, and architectural complications in highergrade HCC (27). In line with our findings, Zhu et al reported a downward shift of D and ADC values from low-to high-grade HCC (8).…”
Section: Discussionsupporting
confidence: 90%
“…IVIM imaging can reflect the characteristics of lesions in terms of cell density, microcirculation perfusion, and tissue complexity (18). As reported previously, a decrease in both ADC and D values may be attributed to the increased cellular density, nuclear-tocytoplasmic ratios, and architectural complications in highergrade HCC (27). In line with our findings, Zhu et al reported a downward shift of D and ADC values from low-to high-grade HCC (8).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a meta-analysis of the use of DWI and IVIM in HCC grading showed the usefulness of D and ADC, but not IVIM parameters [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a meta-analysis ( 52 ) summarized the diagnostic efficacy of ADC value (six studies, 693 HCCs) for well-differentiated HCC, and D (four studies, 304 HCCs) was better than ADC value (13 studies, 1,239 HCCs) in differentiating poorly differentiated HCC (Z = −2.718, P = 0.007). However, some studies ( 15 , 25 , 31 , 33 35 , 38 , 40 , 42 , 49 51 ) were not included in that meta-analysis.…”
Section: Introductionmentioning
confidence: 99%